Effects of Two Modes of Creative Drama on Primary School Pupils’ Achievement in and Attitude to Yoruba Reading Comprehension (2013)
Research findings reveal that pupils‟ achievement in Yoruba language is dwindling with attending negative attitude to the subject. This problem has been traced to teacher - centred method which made pupils to be passive in the learning process. Creative Drama has been identified as a strategy that encourages pupils to be involved in the lesson. Previous studies have also revealed the efficacy of Creative Drama in improving achievement in language skills but hardly can one find any in any of the Nigerian languages. This study therefore determined the effect of two modes of Creative Drama (Story Dramatization and Readers Theatre) on primary school pupils‟ achievement in and attitude to Yoruba reading comprehension. It also determined the moderating effects of school type and gender on the dependent variables. The pretest- posttest, control group, quasi experimental design with a 3x2x2 factorial matrix was adopted. Two hundred and fifty one Primary five pupils randomly selected from three public and three private schools in Ibadan South-East Local Government area of Oyo state were participants. The first and the second experimental groups were treated with Story Dramatisation and Readers Theatre respectively while control group was exposed to conventional instruction for eleven weeks. Instruments used were Yoruba Reading Comprehension Achievement Test (r = 0.80) and Pupils‟ Attitude to Reading in Yoruba Questionnaire (r = 0.81). Seven hypotheses were tested at 0.05 level of significance. Data were analysed using Analysis of covariance and Scheffe post-hoc test. Treatment had significant effects on pupils‟ achievement in Yoruba reading comprehension (F(2,120) = 3.27; p < .05) and attitude (F (2,120) = 10.72; p < .05). Pupils in Readers Theatre group obtained higher achievement score ( = 11.59) followed by those in Story Dramatisation (= 11.41) while the control group had the lowest ( = 10.93). On Pupils‟ attitude to Reading in Yoruba, Pupils exposed to Readers Theatre had higher score ( = 24.39), followed by Story Dramatisation ( = 22.79) and lastly the control group ( = 21.36). School type and Gender had no significant effect on pupils‟ achievement in and attitude to Yoruba reading comprehension. The 2-way interaction effect of school type and gender on pupils‟ achievement in Yoruba reading comprehension is significant (F (1.120) = 6.17; p < .05). Also the 3-way interaction effect of treatment, school type and gender on pupils achievement in Yoruba reading comprehension is significant (F (1.120) = 3.43; p < .05). Readers Theatre and Story Dramatisation were effective at improving pupils‟ achievement and in enhancing their attitude to Yoruba reading comprehension. This study has therefore provided an alternative method of teaching the subject. The two instructional strategies should be employed by teachers in teaching Yoruba reading comprehension.